Effect of computer simulation and animation-integrated instruction on pre-service science teacher trainees conceptual understanding and retention of Acid-Base Chemistry and Stoichiometry - Eshetu Desalegn Alemneh; Dereje Andargie Kidanemariam; Solomon Melesse Mengstie; Belete Bedemo Beyene (OmniaScience, 2024)
The study aimed to investigate the effect of computer simulation and animation-integrated instruction on pre-service science teacher trainees' conceptual understanding and retention of acid-base chemistry and stoichiometry. A quantitative approach with a pretest-posttest-delayed test quasi-experimental design was used. In the study area, there were only two sections of first-year trainees in the natural science department. So a comprehensive sampling technique of the two intact sections was employed. The two intact classes were randomly assigned to an intervention group (IG) and a comparison group (CG). Data was collected using Acid-Base Chemistry and Stoichiometry Conceptual Understanding of a two-tier multiple-choice Test (ABSCUT). Parametric statistics (independent sample t-test and ANCOVA) were used for the data analysis. The independent sample t-test was used for the pre-test analysis to examine the prerequisite experiences of trainees in the two groups and male and female trainees in the IG before the intervention. The result showed no significant difference between the mean score of the CG and IG. The result also showed no significant difference in the mean score of male and female trainees in the IG. The ANCOVA was used for post-test and delayed test analysis after the intervention. The result indicated that there was a statistically significant difference between the two groups on conceptual understanding, F (1, 49) =5.07, p=.029, partial eta squared=0.094, in favor of IG. This tends to imply the concepts of the trainees who received the intervention outperformed the comparison group. The ANCOVA result also indicated that gender difference has no statistically significant difference in the IG, F(1,24)=3.68, p=.067. The delayed-test analysis showed that the IG has higher retention than the CG. Based on the results, this study recommended that policymakers, chemistry curriculum experts, chemistry curricular material developers, and practitioners alike consider the application of computer simulation-integrated chemistry instruction to enhance learners' conceptual understanding and retention.